1996
DOI: 10.1507/endocrj.43.517
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Intercellular Adhesion Molecule-1 Concentrations in Patients with Subacute Thyroiditis and in Patients with Graves' Disease with or without Ophthalmopathy.

Abstract: Abstract. Increased circulating soluble ICAM-1 (sICAM-1) levels has been previously reported in Graves' disease (GD) patients with or without ophthalmopathy (GO) and in patients with toxic nodular goiter but not in patients with subacute thyroiditis. Conflicting results have also been reported about the usefulness of sICAM-1 levels as a marker for the activity of hyperthyroidism.We have therefore determined sICAM-1 levels by a sandwich enzyme linked immunosorbent assay (ELISA) method in 10

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…In one study, the mean sICAM-1 concentration in patients with hypothyroidism due to chronic thyroiditis was significantly elevated versus control subjects and not different from untreated hyperthyroid patients [40]. Other authors reported an increase in sICAM-1 levels in both hyperthyroidism and hypothyroidism, while patients with euthyroid nodular goiter were within the normal range [41].…”
Section: Discussionmentioning
confidence: 93%
“…In one study, the mean sICAM-1 concentration in patients with hypothyroidism due to chronic thyroiditis was significantly elevated versus control subjects and not different from untreated hyperthyroid patients [40]. Other authors reported an increase in sICAM-1 levels in both hyperthyroidism and hypothyroidism, while patients with euthyroid nodular goiter were within the normal range [41].…”
Section: Discussionmentioning
confidence: 93%
“…This overlap was not found in earlier studies. In the case of sICAM‐1, this might have been caused by selection of patients and controls [8], because less overlap may be expected if controls are predominantly non‐smokers as opposed to smoking patients who, because they smoke, may also have more severe GO [7,9,20]. In the group of Graves’ thyroid disease patients without GO, the difference between smokers and non‐smokers was less marked, probably because of small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble forms of these adhesion molecules can be measured in serum, and several studies report that patients with GO have higher levels of sICAM‐1 and sELAM‐1 in serum than patients with Graves’ disease without GO or healthy controls [7–9]. This has attracted our attention, because a serum marker for GO would be very helpful.…”
Section: Introductionmentioning
confidence: 99%
“…Die prim~iren Zielstrukturen des autoreaktiven Immunsystems im Orbitagewebe und die pathogenetischen Zu-sammenh~inge zwischen endok¡ Orbitopathie und autoimmuner Thyreopathie sind bislang unbekannt. Ebenso ist das 16sliche Adhiisionsmolekª ICAM-I in Seren vermehrt nachweisbar, wie in einer Studie mit 130 Patienten gezeigt werden konnte [13], und spiegelt unabhlin~g von der Schilddrª den Grad der orbitalen Entzª vit~t wider [23,56]. Verschiedene immunotaktische Komponenten, wie das Adh~isionsprotein ICAM-1, Hitzeschockproteine und die Expression von HLA-DR-Antigenen lassen sich retrobulbfir nachweisen [1].…”
Section: Abbildung 2aunclassified